Optimasi Kontrol Suhu Tungku Pemanas Menggunakan Metode Firefly Algorithm (FA) - Febrian Rizal Anas; Dwi Ajiatmo; Hidayatul Nurohmah; Machrus Ali (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
A furnace is a piece of equipment used to heat or change shape. Process control is becoming increasingly important in industry, as a consequence of global competition. Year after year, furnaces have progressed in both industrial processes and equipment. The tuning process ensures that system performance meets operating objectives. Intelligent control based on Artificial Intelligent (AI) has developed a lot to improve conventional control to control voltage loads and is always under constant variable assessment. The research results show that the best optimization method is produced by the PID-FA method which produces overshoot = 0.0721, undershoot 0.0081, and settling time at 30.4283 seconds. The PID-FA method produces better performance, according to the desired settings, so that fuel use can have a high level of efficiency